The early gephuroceratid ammonoids from the Roteisenstein Formation of Dillenburg (Cephalopoda, Ammonoidea) - Korn, Dieter; Bockwinkel, Jürgen (European Journal of Taxonomy, 2022)
The ammonoids of the suborder Gephuroceratina from the Roteisenstein (Red Ironstone) Formation of the area around Dillenburg (eastern Rhenish Mountains) are revised, mainly based on historical collections stored in the Museum für Naturkunde, Berlin. The new species Ponticeras materni sp. nov. is described and the species Pseudoprobeloceras pernai (Wedekind, 1918), Pseudoprobeloceras applanatum (Wedekind, 1918), Ponticeras aequabile (Beyrich, 1837), Darkaoceras galeatum (Matern, 1931), Taouzites acutus (Matern, 1931), Koenenites lamellosus (Sandberger & Sandberger, 1851), Acanthoclymenia forcipifera (Sandberger & Sandberger, 1851) and Acanthoclymenia planorbis (Sandberger & Sandberger, 1851) are revised. The stratigraphic distribution of the genera is discussed; they are assigned to three assemblages: (1) Pseudoprobeloceras pernai Zone (latest Givetian; genera Pseudoprobeloceras, Ponticeras, Darkaoceras and Taouzites), (2) Koenenites lamellosus Zone (early Frasnian, containing Koenenites lamellosus and Acanthoclymenia forcipifera) and (3) Mesobeloceras kayseri Zone (middle Frasnian, containing Acanthoclymenia planorbis).